Degree of chitosan deacetylation on thermophysiological comfort properties of nylon 6, 6 fabrics. Issue 5 (2nd September 2019) - Varan, Nilüfer Yıldız; Durur, Güngör
Abstract : Purpose: The purpose of this paper is to analyze the effects of treatments using chitosan in different degree of deacetylations (DDs) on thermophysiological comfort properties of nylon 6, 6/elastane pressure garments using a large skin model hot plate instrumentation to prevent infection and excess sweating during burn scar management for future designs. Design/methodology/approach: Chitosans in different DD (DD 70, DD 81 and nylon 6, 6/elastane fabrics in different structures, then the total DD 90) are treated with thermal resistance ( R ct ) ((°ΔC)(m 2 )/W), total heat loss ( Q t or THL) (W/m 2 ), apparent total evaporative resistance (R e t A ), ((ΔkPa)(m 2 )/W), apparent intrinsic evaporative resistance (R e f A ), ((ΔkPa)(m 2 )/W) and total insulation values ( I t ) (clo) were analyzed using the large skin model hot plate instrumentation in comparison with untreated control samples. Antimicrobial activities, washing tests and moisture regain properties were also evaluated. Findings: It is found that chitosan DDs have a significant effect on thermophysiological comfort properties of nylon 6, 6 fabrics. A small but statistically significant decrease was observed in thermal resistance ( R ct ) (Tog) and isolation ( I t ) (clo) properties for higher chitosan DDs and for higher chitosan concentrations for all fabric samples after each treatment. Antimicrobial activity showed a small but statistically significant decrease for all samples with the increase of DD and fabrics treated with lower DD 70 of chitosan showed better antimicrobial activity for all samples. Additionally, fabrics treated with higher DD's exhibited higher moisture regain. Originality/value: Treatments with chitosan in different DD and in different concentrations impact the heat and moisture transfer properties of nylon 6, 6 fabrics significantly. It is a reference to evaluate the thermophysiological comfort properties of pressure garments for future designs using dry and sweating skin tests while imparting antimicrobial activity with chitosans in different DDs.